Does Dapagliflozin influence arterial stiffness and levels of circulating anti-aging hormone soluble Klotho in people with type 2 diabetes and kidney disease? Results of a randomized parallel group clinical trial - Karalliedde, Janaka; Fountoulakis, Nikos; Stathi, Dimitra; Corcillo, Antonella; Flaquer, Maria; Panagiotou, Angeliki; Maltese, Giuseppe; Mangelis, Anastasios; Ayis, Salma; Gnudi, Luigi (Frontiers in Cardiovascular Medicine, 2022)
Objective: The mechanisms that explain the cardio-renal benefits of sodium glucose co-transporter 2 (SGLT-2) inhibitors are unknown. The effect of SGLT-2 inhibitors on arterial ageing, measured by Aortic Pulse Wave Velocity (Ao-PWV) and Soluble Klotho (s-Klotho), a circulating anti-ageing biomarker of arterial health are also unclear. Design/Setting: A 24-week single center randomised controlled trial (registry number/ EudraCT Number: 2013-004042-42) comparing Dapagliflozin and Ramipril (D+R) versus Ramipril (R) on the primary endpoint of urine albumin excretion rate (AER) and pre-specified secondary endpoints of Ao-PWV and biomarkers of arterial ageing [s-Klotho and Fibroblast Growth Factor 23 (FGF-23)]. People with type 2 diabetes who had estimated glomerular filtration rate (eGFR)>60 ml/min and residual microalbuminuria on maximum tolerated renin angiotensin system (RAS) inhibition were included in this study. Results: In total, 33 participants (male 73%) were randomized to either D+R (n=17) or R (n=16) arms. After 24 weeks of treatment, Ao-PWV (mean ±SD) did not change significantly from baseline D +R [9.06 ±1.91 m/s to 9.13 ±2.03 m/s], and R [9.88 ±2.12 m/s to 10.0 ±1.84 m/s]. AER fell significantly by 43.5% (95% CI: -57.36%, -29.56%; p <0.01) in people in the D+ R arm only. We do not observe any significant changes in FGF-23 or s-Klotho. HbA1c and Angiotensin 1-7 fell significantly only in D + R arm. Conclusions: The combination of Dapagliflozin and Ramipril had no effects on Ao-PWV and s-Klotho which are biomarkers of arterial ageing and cardio-renal risk. Our data suggest that the early cardio-renal benefits observed with SGLT-2 inhibitors are unlikely to be related to an improvement in arterial ageing.